Private equity challenge - investment committee paper - de Longhi - company & market overview - Oliva, Pedro Miguel Paiva Brandão Figueiral de (2022)
This work project consists of an investment committee paper on De’ Longhi, one of the world’s leading firms in the manufacturing of high-end small domestic appliances. Throughout the paper, several value creation strategies are proposed, based on the analysis of the capabilities and resources of the firm and the markets in which it operates. In the final section, the returns for this investment are estimated under different operating scenarios and the potential exit options are discussed.